A Family Story as a Horizon of Human Identity. On the Example Szuflada (The Drawer) by Katarzyna Szczepańska-Kowalczuk - Gontarz, Beata (Sensus Historiae, 2020)
The purpose of the article is to present, on the example of Katarzyna SzczepańskaKowalczuk’s book, the identity that is shaped during the preparation and narrative elaboration on a family history. The result of these activities is the literary form of the modern non-fiction saga, created by women on the basis of family documents. The family history appears to be not ready, being in the process of ordering, also reveals the person who makes the selection, choice, reconstruction, who narrates. Understood after Paul Ricoeur, the narrative identity of the authors (“to answer the question ‘who?’ Is to tell the story of life”) in the case of family stories is constituted at the interface between the identity of the experiencing subject (ipse) and an entity identical with another (idem) – a result is a kind of autobiography: “The subject also appears as a reader and author of his own life”. The second aspect of considering the identities of the authors who create contemporary non-fiction family saga is the proposal of Charles Taylor, who justifies the need to build identity by placing the subject in relation to the moral horizon shaped in a dialogue with authorities, in the “horizon of significant others”.